2022
DOI: 10.1002/qua.27081
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of metal (Ni, Cu) doped cobalt phosphide catalysts and mechanism of catalytic hydrogen evolution of NH3BH3

Abstract: In this paper, using density functional theory (DFT) methods, we meticulously investigated the structural properties of cobalt phosphide (CoP) and its Cu‐ and Ni‐doped counterpart. Then, on the surfaces of three catalysts, the hydrogen evolution reaction mechanism of ammonia borane (NH3BH3) was examined in turn, and four possible hydrogen evolution reaction paths of NH3BH3 on the catalyst surface were reviewed. The optimal reaction channel for each catalyst was found by comparing the activation energies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…12 Cu-doped CoP could realize efficient catalytic HER. 13 Ti-based MOFs (Ti-MOFs) can be used as a favorable candidate catalyst for the photocatalytic HER. 14 It is demonstrated that transition metal doping is effective for the improvement of W 2 C catalyst activity.…”
Section: Introductionmentioning
confidence: 99%
“…12 Cu-doped CoP could realize efficient catalytic HER. 13 Ti-based MOFs (Ti-MOFs) can be used as a favorable candidate catalyst for the photocatalytic HER. 14 It is demonstrated that transition metal doping is effective for the improvement of W 2 C catalyst activity.…”
Section: Introductionmentioning
confidence: 99%